Edukasi dan Pelatihan Pengelolaan Stress dengan Teknik Relaksasi Nafas dalam dan Relaksasi Otot Progresif di UPT Puskesmas Medan Labuhan - Putri, Maidina; Khairani, Khairani (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Psychological well-being is a global issue that is increasingly receiving attention, especially in groups of people who have high workloads and are at risk of experiencing chronic stress requiring attention through promotive and preventive efforts. The purpose of this PkM activity is to provide education and training for participants to manage stress with deep breathing relaxation techniques and progressive muscle relaxation at the Medan Labuhan Community Health Center UPT. The implementation method for this PkM activity is in the form of education, counseling and training in deep breathing relaxation and progressive muscle relaxation. The implementation of this PkM is divided into 3 parts, namely, preparation of activities, implementation of activities and evaluation. The results of this PkM activity on the level of knowledge of the participants are seen from the results after being given knowledge of deep breathing relaxation and progressive muscle relaxation on the post-test results. Most understand the knowledge of deep breathing relaxation and progressive muscle relaxation, namely in the good category as many as 11 respondents (92%), after progressive muscle training the stress level of the participants is in the mild category as many as 10 respondents (83%).